Role of Sphingosine-1-Phosphate in Mast Cell Functions and Asthma and Its Regulation by Non-Coding RNA - Saluja, Rohit; Kumar, Ashok; Jain, Manju; Goel, Sudhir K.; Jain, Aklank (Frontiers in Immunology, 2017)
Sphingolipid metabolites are emerging as important signaling molecules in allergic diseases specifically asthma. One of the sphingolipid metabolite, sphingosine-1-phosphate (S1P), is involved in cell differentiation, proliferation, survival, migration, and angiogenesis. In the allergic diseases, alteration of S1P levels influences the differentiation and responsiveness of mast cells (MCs). S1P is synthesized by two sphingosine kinases (SphKs), sphingosine kinase 1, and sphingosine kinase 2. Engagement of IgE to the FcεRI receptor induces the activation of both the SphKs and generates S1P. Furthermore, SphKs are also essential to FcεRI-mediated MC activation. Activated MCs export S1P into the extracellular space and causes inflammatory response and tissue remodeling. S1P signaling has dual role in allergic responses. Activation of SphKs and secretion of S1P are required for MC activation; however, S1P signaling plays a vital role in the recovery from anaphylaxis. Several non-coding RNAs have been shown to play a crucial role in controlling the MC-associated inflammatory and allergic responses. Thus, S1P signaling pathway and its regulation by non-coding RNA could be explored as an exciting potential therapeutic target for asthma and other MC-associated diseases.